The relationship between safety management practices and safety performance among warehouse employees of a distributor company in Malaysia - Shanthini, Arumugam (2021)
Safety performance is an important element for occupational safety and health (OSH) and normally measured by accident and injury rate. However, several scholars advocate that safety performance should be measured by leading indicator namely safety behaviour to indicate the standard of OSH level of an organisation. Since decades, the determinants of safety performance in terms of safety behaviour has been studied as safety behaviour was revealed as the substantial factor towards workplace accidents. Safety management has been revealed as the key factor for safety performance, for both reactive and proactive measures. Additionally, previous literature also determined that supervisor roles in managing safety influenced safety performance. Therefore, this research studied the relationship between safety management of employers as well as supervisors and safety performance of workers in company XY. Adapting previous research, safety management was measured by four variables namely safety policy, safety concern, safety motivation and supervisor safety roles. Also based on previous research, safety performance was measured by two dimensions of safety behaviour namely safety compliance and safety participation. A set of self-administered questionnaires we distributed to 200 respondents in Company XY and 186 of them were usable for this study. Furthermore, Partial Least Square- Structural Equation Model (PLS-SEM) analysis was applied to assess the measurement model and structural model. The data analysis confirmed the validity of the measurement model, and the hypothesis testing revealed the significant effect of safety management in terms of safety policy, safety concern, safety motivation, and supervisor safety on safety compliance as well as safety participation respectively. In conclusion, this research results showed that an improved safety management could influence safety performance among workers. This research also offers contributions to the body of knowledge in terms of providing empirical evidence on the effect of safety management on safety behaviour besides becoming a complementary reference to the practitioners of OSH to improve safety performance in their organisations.